2022
DOI: 10.1371/journal.pone.0270040
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoproteomics identifies beaver fur in Danish high-status Viking Age burials - direct evidence of fur trade

Abstract: Fur is known from contemporary written sources to have been a key commodity in the Viking Age. Nevertheless, the fur trade has been notoriously difficult to study archaeologically as fur rarely survives in the archaeological record. In Denmark, fur finds are rare and fur in clothing has been limited to a few reports and not recorded systematically. We were therefore given access to fur from six Danish high status graves dated to the Viking Age. The fur was analysed by aDNA and palaeoproteomics methods to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In this work, the species of origin was identified for most of the samples studied, although the results highlighted the limits of available protein sequences in public databases. This is a known problem for wild species identification in archaeological materials 11 . For example, the proteomic results suggested that a species of seal was the source of the gut skin for both the more recent Parka R, and Gut skin jacket A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the species of origin was identified for most of the samples studied, although the results highlighted the limits of available protein sequences in public databases. This is a known problem for wild species identification in archaeological materials 11 . For example, the proteomic results suggested that a species of seal was the source of the gut skin for both the more recent Parka R, and Gut skin jacket A.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limits, over the past few years paleoproteomics has gained more and more relevance 9 . Specifically, it has been used to identify clothing material from several contexts, such as Bronze Age sites along the Silk Road 10 , Viking Age Denmark 11 , and Pre-Columbian Peru 12 . The garment proteins identified are mainly keratins from fur, or collagen from skin 13 , and, less frequently, hollow organ sub-mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were then vacuum-centrifuged to remove the ACN. Samples were then resuspended in 12 μL of 5% ACN 0.1% trifluoroacetic acid (TFA) and analysed by LC-MS/MS based on previously published protocols for palaeoproteomic samples [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another important issue in phyloproteomics is the relative scarcity of proteomic datasets [18, 19]. There are currently tens of thousands of publicly available whole genome sequences, covering hundreds of species [20, 21, 22, 23, 24].…”
Section: Statement Of Needmentioning
confidence: 99%